Analysis of the Influence of Social Media Engagement, Ethical Branding, and Cultural Fit on Brand Authenticity Perception in the Food and Beverage Industry - Tanti Widia Nurdiani; Riesna Apramilda; Tyahya Whisnu Hendratni; Dewi Putri Anjar Wulan; Sonya Sidjabat; Sukma Irdiana (Journal of Innovative and Creativity, 2025)
This study was conducted to evaluate the extent to which consumer engagement on social media, the application of ethical values ​​in brand strategy, and cultural fit influence perceptions of brand authenticity in the food and beverage industry. This study used a quantitative approach with a survey method involving 200 respondents. Participants were selected based on certain criteria, such as being at least 18 years old, actively using social media, following the official accounts of food and beverage brands in the past six months, and having experience purchasing products from brands promoted digitally. Partial analysis also revealed that social media engagement, ethical branding, and cultural fit each positively contribute to perceptions of brand authenticity. The higher the consumer engagement on social media, the more consistent the ethical practices implemented, and the more relevant the brand values ​​are to the consumer's culture, the stronger the authentic image formed. These findings enrich the academic discourse in the field of marketing and branding, while also providing practical guidance for business actors in building authentic, relevant, and resilient brand strategies in the increasingly complex competition of the food and beverage industry.